1998
DOI: 10.1007/s004360050496
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum in regulating the Entamoeba histolytica cell cycle: a flowcytometric analysis

Abstract: To identify stage-specific molecules that might be important in pathogenicity, we focused on synchronizing Entamoeba histolytica HM1:1MSS axenic cultures by serum deprivation. By growing trophozoites in medium containing 2% serum for 16 h and then replacing with complete medium, we found that most of the trophozoites were in the G0/G1 phase of the cell cycle. Subsequently, the distribution of trophozoites in G0/G1, S and G2/M phases was studied for up to 24 h and it was observed that after 8 h, the trophozoite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…EhDead1 mRNA is over expressed in S phase of cell cycle EhDEAD1 exhibits 70% homology to yeast DED1 RNA helicase (Table 1), which participates in cell cycle regulation (Warbrick and Glover, 1994;Forbes et al, 1998;Grallert et al, 2000). Although axenic cultures of E. histolytica are made of a heterogeneous population of cells with varying DNA content, various studies have described cell cycle phases in log phase cultures in distinct strains or clones (Orozco et al, 1988;Dvorak et al, 1995;Gangopadhyay et al, 1997;Vohra et al, 1998;Das and Lohia 2002;Dastidar et al, 2007). Here, we used trophozoites of clone L6, which is routinely synchronized by the mitotic blocker colchicine in our laboratory and whose cell cycle phases lasting is well characterized (Orozco et al, 1988;Marchat et al, 2003).…”
Section: Rehdead1 48 Has Atp-dependent Rna Unwinding Activity In Vitromentioning
confidence: 97%
See 2 more Smart Citations
“…EhDead1 mRNA is over expressed in S phase of cell cycle EhDEAD1 exhibits 70% homology to yeast DED1 RNA helicase (Table 1), which participates in cell cycle regulation (Warbrick and Glover, 1994;Forbes et al, 1998;Grallert et al, 2000). Although axenic cultures of E. histolytica are made of a heterogeneous population of cells with varying DNA content, various studies have described cell cycle phases in log phase cultures in distinct strains or clones (Orozco et al, 1988;Dvorak et al, 1995;Gangopadhyay et al, 1997;Vohra et al, 1998;Das and Lohia 2002;Dastidar et al, 2007). Here, we used trophozoites of clone L6, which is routinely synchronized by the mitotic blocker colchicine in our laboratory and whose cell cycle phases lasting is well characterized (Orozco et al, 1988;Marchat et al, 2003).…”
Section: Rehdead1 48 Has Atp-dependent Rna Unwinding Activity In Vitromentioning
confidence: 97%
“…Next, DNA synthesis was inhibited by serum starvation in transfected and non-transfected trophozoites (Vohra et al, 1998) and then, cell cycle reactivation was induced by addition of fresh medium and DNA content was analyzed by flow cytometry ( Fig. 7D and E).…”
Section: Rehdead1 48 Has Atp-dependent Rna Unwinding Activity In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were kept for 2 h in BI-S-33 lacking BS, ammonium ferric citrate (AFC) and cysteine in order to synchronize the culture (Vohra et al, 1998). Amoebas (10 4 ) were inoculated into 1 ml BI-S-33 or low-iron with or without holoLf incubated for 96 h, and samples were collected every 24 h to test cell viability by trypan blue exclusion, using light microscopy.…”
mentioning
confidence: 99%
“…Estimation of genome content was based on fluorescence of DNA binding dye either by flow cytometry (whole cell genome content) or scanning cytometry (individual nuclear genome content). Increased heterogeneity was observed in late log phase culture, suggesting that depletion of nutrients maybe responsible for loss of cell cycle control (Gangopadhyay et al 1997a, Vohra et al 1998. However, later studies showed that genome reduplication occurred within 2 h after initiation of DNA synthesis in freshly cultured synchronized cells .…”
Section: Genome Reduplication Occurs Commonly In Entamoeba Trophozoitesmentioning
confidence: 90%